1989
DOI: 10.1103/physrevlett.63.1641
|View full text |Cite
|
Sign up to set email alerts
|

Electron gas in semiconductor multiple quantum wires: Spatially indirect optical transitions

Abstract: In optical experiments with laterally patterned GaAs quantum wells we observe confinement of free carriers to motion in one dimension. Optical recombination of band-gap transitions shows that free electrons and holes are confined in spatially indirect type-II multiple quantum wires. Resonant-inelasticlight-scattering spectra show intersubband excitations of the one-dimensional electron gas. From the optical measurements we obtain the Fermi energy as well as subband spacings and determine the linear free-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…There are also very interesting Raman experiments on quantum wires and dots. [6][7][8][9][10][11][12][13] Strenz et al reported on SPE in quantum wires and observed SPE in dots. 11 Onedimensional electron systems which are nearly in the 1D quantum limit have been investigated by Schmeller et al 9 They found that the relative energy renormalizations of the 1D intersubband SDE and CDE with respect to the simultaneously observed corresponding SPE are quite similar to those found for 2D systems.…”
Section: P Grambow and K Eberlmentioning
confidence: 95%
“…There are also very interesting Raman experiments on quantum wires and dots. [6][7][8][9][10][11][12][13] Strenz et al reported on SPE in quantum wires and observed SPE in dots. 11 Onedimensional electron systems which are nearly in the 1D quantum limit have been investigated by Schmeller et al 9 They found that the relative energy renormalizations of the 1D intersubband SDE and CDE with respect to the simultaneously observed corresponding SPE are quite similar to those found for 2D systems.…”
Section: P Grambow and K Eberlmentioning
confidence: 95%
“…This reduction results in a concentration of the density of states at the band edge and in reduced scattering in the remaining directions of free motion, which is both of interest for optical and electrical devices such as laser diodes and fast transistors. [1][2][3][4] It can be achieved by structural sizes in the nanometer range, resulting in an energy difference of the confined states larger than both the thermal energy and the excitonic binding energy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have been devoted to the probing of quasi-2DEG and quasi-1DEG energy spectrum using different techniques such as Fourier transform infrared spectroscopy ͑FTIR͒, [36][37][38][39][40][41][42][43][44][45][46][47][48] Raman scattering spectroscopy, [49][50][51][52][53][54][55][56][57] far-infrared ͑FIR͒ laser spectroscopy [58][59][60] and photoluminescence. [61][62][63][64][65][66][67][68][69][70] In all these techniques a collective excitation of the 1DEG is measured, the Raman scattering also giving information about single particle excitations. There is a large diversity of theoretical treatments for the optical response of an electron gas in reduced dimensionality, ranging from classical hydrodynamic to quantum manybody approaches.…”
Section: Introductionmentioning
confidence: 99%